Identifying and Helping Struggling Readers - Hairston, Antonio (Journal of the American Academy of Special Education Professionals, 2011)
How do children excel in learning if they struggle with the basics of reading? The question of helping struggling readers shows progress and broadening their minds with intelligent information is being researched every day. Research suggests that there are many strategies and interventions for students achieving below their reading grade level that can be utilized to promote reading effectiveness and mastery. Research also underscores that students must have a strong foundation in reading in order to adequately progress from grade level to grade level. There is an enormous amount of emphasis bestowed on our nation regarding the importance of reading; however, there are still many struggling readers in our country today. Teachers must recognize signs of struggling readers and provide relevant interventions and strategies that lead to quality reading.